DOES COVID-19 EFFECT BANK PERFORMANCE? An Evidence from Indonesia - Johan, Suwinto; Chuadrey, A. Letizia M. (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The Covid-19 epidemic has impacted many elements of human existence. The economy is in a downturn. The number of individuals living in poverty is rising. Many businesses are going out of business. Banking is a sector that helps a country's economy. The goal of this study is to see if COVID-19 impacts the banking industry's performance. The data for this study spans two years, from 2019 to 2020. The year before the pandemic is 2019, and the pandemic is 2020. This study includes data from 17 banks as a sample. The Mann-Whitney non-parametric test method was employed in this investigation. The study looks at any changes in bank financial performance in Indonesia before and after the Covid-19 outbreak. According to the findings, bank performance in company size, profitability, and efficiency did not alter before or during the pandemic. This explains why the bank's performance is stable due to the government's macroeconomic policies. Bank success has been sustained by macro policies